Epistemic Emotions Justified - Laura Silva (Philosophies, 2022)
The view that emotions can provide defeasible justification for evaluative beliefs is widespread in the emotion literature. Despite this, the question of whether epistemic emotions can provide defeasible justification for theoretical beliefs has been almost entirely ignored. There seems to be an implicit consensus that while emotions may have justificatory roles to play in the former case, they have no such roles to play in the latter case. Here, I argue against this consensus by sketching a proposal for securing epistemic emotions justificatory roles.